2016
DOI: 10.1038/srep30559
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Energy of Snoring Sounds Are Associated with Common Carotid Artery Intima-Media Thickness in Obstructive Sleep Apnea Patients

Abstract: Obstructive sleep apnea (OSA) is a known risk factor for atherosclerosis. We investigated the association of common carotid artery intima-media thickness (CCA-IMT) with snoring sounds in OSA patients. A total of 30 newly diagnosed OSA patients with no history of cardiovascular diseases were prospectively enrolled for measuring mean CCA-IMT with B-mode ultrasonography, body mass index, metabolic syndrome, 10-year cardiovascular disease risk score, high-sensitivity C-reactive protein, and homocysteine. Good-qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…8). This finding is consistent with the characteristics of stenotic-typed snoring that generates an irregular sound and peak frequencies over 500 Hz [64]. Considering the sine-dynamic case in particular, the peak frequencies occur in the range of 200–300 Hz (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…8). This finding is consistent with the characteristics of stenotic-typed snoring that generates an irregular sound and peak frequencies over 500 Hz [64]. Considering the sine-dynamic case in particular, the peak frequencies occur in the range of 200–300 Hz (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Considering the proximity of the sound source to the carotid artery, chronic laryngeal snoring can initiate or aggravate the carotid artery wall thickening. Moreover, carotid atherosclerosis is significantly associated with snoring sound energy from 0 to 20 Hz [64]. This study predicted the highest sound pressure levels in this range, which are 10–20 dB higher than those of other frequencies, as shown in Figs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A recent study by Lee et al found that snoring sounds may cause carotid wall thickening, as shown by ultrasound measurement of CCA intima‐media thickness . In fact, the specific frequencies of 0 to 20 Hz and 652 to 1,500 Hz correlated most with CCA intima‐media thickening, which suggests that the etiology of the thickening is likely more complex and multifactorial.…”
Section: Discussionmentioning
confidence: 93%
“…Acute physiological consequences of OSA, such as intermittent hypoxia, swings in intrathoracic pressures, and repetitive arousals leading to sympathetic activation are some of the proposed mechanisms by which OSA may contribute to an accelerated rate of endothelial dysfunction, oxidative stress, and atherosclerosis over time [43]. Exposure to chronic snoring vibrations may also trigger an inflammatory cascade leading to endothelial damage, thus contributing to early development of atherosclerosis [4447]. By relieving some of the acute physiologic consequences of OSA, CPAP therapy may thereby eliminate some of the triggers leading to accelerated atherosclerosis and vascular inflammation overtime.…”
Section: Discussionmentioning
confidence: 99%